Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Bermain Lempar Bola Kreweng di TK Negeri Pembina 1 Mojosari - Lestari Aprilianti; Sri Setyowati (Journal on Education, 2023)
Early childhood children need to be provided with age-appropriate and ability-appropriate stimulation, and one aspect that needs to be developed is gross motor skills. The purpose of this study is to improve gross motor skills using the activity of playing "kreweng" ball throwing. The research method used is Classroom Action Research (CAR). The subjects in this study were 17 children aged 5-6 years from Group B2 of TK Negeri Pembina 1 Mojosari. The data collection techniques used in this study were observation sheets and documentation. The data analysis technique used by the researcher is quantitative and qualitative descriptive analysis. The results of this Classroom Action Research (CAR) study showed that in the pre-action phase, 2 children (12%) had shown significant progress, then in Cycle I, the number increased to 9 children (53%), and in Cycle II, it increased to 15 children (88%). In terms of the ability to throw accurately, in the pre-action phase, 1 child (6%) had shown significant progress, in Cycle I, it increased to 9 children (53%), and in Cycle II, it increased to 14 children (82%). In terms of the ability to throw with distance, in the pre-action phase, 3 children (18%) had shown significant progress, in Cycle I, it increased to 9 children (53%), and in Cycle II, it increased to 14 children (82%). It can be concluded that playing "kreweng" ball throwing has been able to improve the gross motor skills of 5-6-year-old children in Group B at TK Negeri Pembina 1 Mojosari.